Kilka uwag dotyczących realizacji funkcji postępowania cywilnego na tle funkcji prawa - Jędrejek, Grzegorz (Kwartalnik Prawa Publicznego, 2016)
This paper aims to indicate the relationship between the functions of law in general and the functions of civil proceedings, and the question whether the current regulation of civil procedure, contained primarily in the codification of 1964, properly satisfies the implementation of the functions discussed. According to the author, after 1989, the relationship between civil law and procedural law has been shattered. The Code of Civil Procedure is the most extensive act in the Polish language. The accepted model of civil proceedings challenges the possibility of effective redress of claims, or the defense of one’s rights, by a citizen who acts independently, without the assistance of a professional attorney. The existing regulation of civil procedure does not fulfill its function, leading to social tensions, affecting judicial judgment, which, as the survey shows, is critical.